"Roma V’aspetta!" incarichi di padre Martini nella città papale - Pasquini, Elisabetta 1966- (2022)
In the spring of 1753, Padre Martini made his second trip to Rome, to concert his own music for a number of solemn celebrations marking the feast of Saints Philip and James, and the triduum for the beatification of fellow Franciscan Joseph of Cupertino. The music enjoyed an excellent response from the audience; a few months later the composer thus received an unofficial offer from Pope Benedict XIV to take up the position of coadjutor to the maestro at the Cappella Giulia. Equally unofficially, Padre Martini refused this offer, citing ill health. Evidence of his Roman sojourn are found not only in the descriptions appearing in the chronicles of the time, but also in the music performed in that period, including the music he composed especially for the occasion. On the basis of certain indications written in the scores, in fact, we can reconstruct much of this repertoire and thus launch a discussion about the practice of performance and its interweaving with the ceremonial sphere.
Keywords: Giambattista Martini, Giuseppe da Copertino, Cappella Giulia, musica liturgica; Giambattista Martini; Joseph of Cupertino; Cappella Giulia; liturgical music